PESANTREN ON THE FRAME OF GOVERNMENT POLICIES - Moh Kosim (Karsa: Journal of Social and Islamic Culture, 2015)
This article tries to describe government policies toward pesantren, as the Islamic intistitution, which has been existing from the early  Independence of Indonesia period to present times, and its implications on the progresses of pesantren. This study uses library research on related documents of government policies and the result shows that the government policies tend to indicate to be a positive development. In the beginning of old and new orders, government policies were simply in form of unofficial claim above the role of pesantren in accelerating the nation intelligence. Since the release of decree of UU No. 2/1989 pesantren has been approved and legitimated as the subsystem of national education, though, pesantren keeps and maintains its characterisitc. As UU  No. 20/2003 legitimated and followed by relating policies –especilally PP No. 55/1997, PMA No. 13/2014, and PMA No. 18/2014 – pesantren has been totally awarded as part of national educational system, in turn, such of the institution has more freedom in portraying Islamic values by enhancing its characteristic as the institution focusing on tafaqquh fî al-dîn (an attempt to a totally Islamic understandings) and developing the other competences based on the characteristic of each pesantren.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.724